Local abundance and regional distribution of tree species of forest fragments in Brazil: A test of models - Leite, Samuel Jorge (2001)
Patterns of local abundance and regional distribution of tree species were analyzed on three spatialscales and compared with those predicted by Hanski’s 1982 original core-satellite model, Brown’s 1984 nichebasedmodel, and Tokeshi’s 1992 model. Data were collected in seven forest fragments dispersed overapproximately 7200 km2, remnants of a former continuous forest in the south of Mato Grosso do Sul state,southwestern Brazil. Fifty-six east-west-oriented 10 m ¥ 150 m plots were randomly demarcated in thosefragments from 1994 to 1996. In each plot all trees having DBH ≥ 0.15 m were recorded and measured. Thesmallest scale was that of the fragments themselves and the greatest was that of the entire region. No evidencewas found of the bimodality predicted by Hanski’s 1982 model on any scale. On all scales, an unimodal patternwas found whose mode was on the left side (satellite mode) of the distribution. This pattern was in bestagreement with the predictions of Tokeshi’s 1992 model.